ASSESSMENT OF REPRODUOTiVE POTENTiAL OF MEN - N. A. Kurashova (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The article summarizes and analyzes literature data concerning significant degradation of basic indicators of reproductive function of teenage boys and of men of reproductive age. Sharp decrease of fertility and sexual activity of young and middle-aged men is registered in industrialized countries including Russia in recent decades. The results of researches of infertility causes among fertility-challenged couples shows that "male factor" accounts for about a half of the cases. Data about progressing tendency of degradation of children's and adolescents' reproductive health causes particular concern. The diseases of child and adolescent gestation period cause almost a half of the cases of male infertility. The reason of it is the complex of negative factors influencing the population, including growth of stress-producing social factors, sharp aggravation of the ecological situation, increase of quantity of impaired development cases, inadequate use of medicines, alcoholism, smoking, drug addiction and many other things. This situation is considered to be critical, its significance causes carrying out complex researches of reproductive potential of the man population of Russia.